Two Cases of Periprosthetic Atypical Femoral Fractures in Patients on Long-Term Bisphosphonate Treatment - Takanori Miura; Hiroaki Kijima; Takayuki Tani; Toshihito Ebina; Naohisa Miyakoshi; Yoichi Shimada (Case Reports in Surgery)
The current definition of atypical femoral fractures (AFFs) excludes periprosthetic fractures. However, a few cases of bisphosphonates (BPs) -associated periprosthetic atypical femoral fractures (PAFFs) have been reported in the literature. Here, we report two rare cases of PAFFs that fulfilled the major criteria for AFFs in patients with prolonged use of BPs. Both cases progressed to a complete fracture with minor trauma from an incomplete fracture at the distal tip of the well-fixed femoral stem. The femoral stem effect on lateral femoral cortical bone, together with the decreased bone elastic resistance induced by BPs, was considered the cause of onset. In each case, we performed open reduction and internal fixation using a locking plate with cable grip and postoperatively prescribed teriparatide and low-intensity pulsed ultrasound (LIPUS). Both cases had a good clinical course. However, as conservative treatment was not effective in these cases, treatment such as non-weight-bearing exercises during hospitalization or prophylactic surgery may be necessary. Further studies are needed to determine the optimal treatment strategy.